2016
DOI: 10.1073/pnas.1519790113
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure provides insights into evolutionary design and resilience of Coscinodiscus sp. frustule

Abstract: We conducted in situ three-point bending experiments on beams with roughly square cross-sections, which we fabricated from the frustule of Coscinodiscus sp. We observe failure by brittle fracture at an average stress of 1.1 GPa. Analysis of crack propagation and shell morphology reveals a differentiation in the function of the frustule layers with the basal layer pores, which deflect crack propagation. We calculated the relative density of the frustule to be ∼30% and show that at this density the frustule has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…The proposed evolutionary functions for these intricate shell designs include nutrient acquisition, control of diatom sinking rate, control of turbulent flow around the cell, and protection from grazing and viral attack [2]. These patterns have also an unprecedentedly high specific strength, exceeding that of all other reported natural biomaterials, which we attribute to the combination of the honeycomb sandwich plate architecture and extremely low flaw density in the constituent biosilica [1]. The ornamentation pattern of the valve, which are very aesthetic, are use for classifying diatoms.…”
Section: Introductionmentioning
confidence: 97%
“…The proposed evolutionary functions for these intricate shell designs include nutrient acquisition, control of diatom sinking rate, control of turbulent flow around the cell, and protection from grazing and viral attack [2]. These patterns have also an unprecedentedly high specific strength, exceeding that of all other reported natural biomaterials, which we attribute to the combination of the honeycomb sandwich plate architecture and extremely low flaw density in the constituent biosilica [1]. The ornamentation pattern of the valve, which are very aesthetic, are use for classifying diatoms.…”
Section: Introductionmentioning
confidence: 97%
“…Coscinodiscus present a highly structured frustule not only in two dimensions but also in 3-D (Sumper, 2002;Sar et al, 2008;Romann et al, 2015a,b;Aitken et al, 2016;Xing et al, 2017). The valve consists of three overlapping silica layers; the external side named cribrum, it includes smaller porous silica connections called cribellum and finally a third internal layer named foramen.…”
Section: Frustules: Interest For Optical Studiesmentioning
confidence: 99%
“…In the marine environment, the silica frustule made by diatoms which can present extraordinary mechanical strength (Hamm et al, 2003;Aitken et al, 2016), contribute to their mechanical defense against grazers and it was shown that the silicification level can influence interactions between diatoms and grazers (Pondaven et al, 2007;Schultes et al, 2010;Liu et al, 2016), for example heterotrophic dinoflagellates preferentially feed on diatoms with low silica content . The overall density of the silica wall also affects the overall sinking rate of diatoms, and help the cells in escaping from predators and parasites, avoiding high light intensity, or finding new resource areas (Raven and Waite, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Moreover, despite high porosity, diatom silica exhibits remarkably high mechanical stability, which is important for filtration applications. [12][13][14] Controllably changing the pores thus empowers an array of properties, and in turn applications of diatom systems for a wide variety of tasks.…”
Section: Introductionmentioning
confidence: 99%